A COMPARATIVE STUDY OF TERMINOLOGICAL DERIVATION IN ENGLISH AND UZBEK LANGUAGES (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Abstract. This article explores the derivational processes of terminology in English and Uzbek languages. By analyzing affixation, composition, and abbreviation methods used to create new terms, the study highlights both similarities and differences between these two languages. The findings offer insights into linguistic structures and contribute to a deeper understanding of terminological development across languages.